Causes of death among children aged 5–14 years in the WHO European Region: a systematic analysis for the Global Burden of Disease Study 2016. (May 2018) - Kyu, Hmwe H; Stein, Claudia E; Boschi Pinto, Cynthia; Rakovac, Ivo; Weber, Martin W; Dannemann Purnat, Tina; Amuah, Joseph E; Glenn, Scott D; Cercy, Kelly; Biryukov, Stan; Gold, Audra L; Chew, Adrienne; et al.
Summary: Background: The mortality burden in children aged 5–14 years in the WHO European Region has not been comprehensively studied. We assessed the distribution and trends of the main causes of death among children aged 5–9 years and 10–14 years from 1990 to 2016, for 51 countries in the WHO European Region. Methods: We used data from vital registration systems, cancer registries, and police records from 1980 to 2016 to estimate cause-specific mortality using the Cause of Death Ensemble model. Findings: For children aged 5–9 years, all-cause mortality rates (per 100 000 population) were estimated to be 46·3 (95% uncertainty interval [UI] 45·1–47·5) in 1990 and 19·5 (18·1–20·9) in 2016, reflecting a 58·0% (54·7–61·1) decline. For children aged 10–14 years, all-cause mortality rates (per 100 000 population) were 37·9 (37·3–38·6) in 1990 and 20·1 (18·8–21·3) in 2016, reflecting a 47·1% (43·8–50·4) decline. In 2016, we estimated 10 740 deaths (95% UI 9970–11 542) in children aged 5–9 years and 10 279 deaths (9652–10 897) in those aged 10–14 years in the WHO European Region. Injuries (road injuries, drowning, and other injuries) caused 4163 deaths (3820–4540; 38·7% of total deaths) in children aged 5–9 years and 4468 deaths (4162–4812; 43·5% of total) in those aged 10–14 years in 2016. Neoplasms caused 2161 deaths (1872–2406; 20·1% of total deaths) in children aged 5–9 years and 1943 deaths (1749–2101; 18·9% of total deaths) in those aged 10–14 years in 2016. Notable differences existed in cause-specific mortality rates between the European subregions, from a two-times difference for leukaemia to a 20-times difference for lower respiratory infections between the Commonwealth of Independent States (CIS) and EU15 (the 15 member states that had joined the European Union before May, 2004). Interpretation: Marked progress has been made in reducing the mortality burden in children aged 5–14 years over the past 26 years in the WHO European Region. More deaths could be prevented, especially in CIS countries, through intervention and prevention efforts focusing on the leading causes of death, which are road injuries, drowning, and lower respiratory infections. The findings of our study could be used as a baseline to assess the effect of implementation of programmes and policies on child mortality burden. Funding: WHO and Bill & Melinda Gates Foundation.